Fredholmness and index of simplest weighted singular integral operators with two slowly oscillating shifts - Karlovych, Oleksiy (2017)
This work was partially supported by the Fundacao para a Ciencia e a Tecnologia (Portuguese Foundation for Science and Technology) through the project PEst-OE/MAT/UIO297/2014 (Centro de Matemdtica e Aplicacoes). The authors would like to thank the anonymous referee for useful remarks and for informing about the work [5].